Sharīʻa and the concept of benefit : the use and function of Maṣlaḥa in Islamic jurisprudence /: the use and function of Maṣlaḥa in Islamic jurisprudence. (2015) - Āl Saʻūd, ʻAbd al-ʻAzīz ibn Saṭṭām ibn ʻAbd al-ʻAzīz
No abstract available